PENGARUH MOTIVASI WISATAWAN NUSANTARA TERHADAP NIAT BERKUNJUNG KEMBALI KE PANTAI PANDAWA, BALI - Faturrachman, Aqmal; Sudiarta, I Nyoman; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024), 2025)
This research is motivated by the decline in visits to the Pandawa Beach tourist destination, seen in 2021 the number of domestic tourists visiting was 362,167, this number is very far from the number of visits in 2019 of 1 million tourists. The purpose of this study is to determine the effect of Push Motivation and Pull Motivation on the intention of tourists to revisit Pandawa Beach. The study used quantitative methods. Data were collected using questionnaire and interview data collection techniques. Respondents in this study were 80 respondents with the criteria of respondents being domestic tourists who traveled from their place of residence for at least 24 hours and domestic tourists who had or were visiting Pandawa Beach with an age range of 21 - 40 years. The results of the study can be concluded that the Push Motivation variable has a positive and significant effect on the intention to revisit with a coefficient of 0.074 (7.4%), the Pull Motivation variable has a positive and significant effect on the intention to revisit with a coefficient of 0.218 (21.8%), and the Push Motivation and Pull Motivation variables simultaneously show a positive and significant effect with a coefficient of determination of 0.22 (22%).